2008
DOI: 10.1039/b712710c
|View full text |Cite
|
Sign up to set email alerts
|

Soft-landing of peptide ions onto self-assembled monolayer surfaces: an overview

Abstract: This review is focused on what has been learned in recent research studies concerned with fundamental aspects of soft-landing and reactive landing of peptide ions on self-assembled monolayer surfaces (SAMs). Peptide ions are particularly attractive model systems that provide important insights on the behavior of soft landed proteins, while SAMs provide a convenient and flexible platform for tailoring the interfacial properties of metals and semiconductor surfaces. Deposition of mass-selected ions on surfaces i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
169
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 115 publications
(184 citation statements)
references
References 79 publications
4
169
0
11
Order By: Relevance
“…This potential accurately describes the short-range, repulsive interactions which determine the collisional energy-transfer, but not the longrange intermolecular potential. The latter describes the attractive interaction of the peptide ion with the surface and is necessary to model soft-landing experiments [23,24] in which the ion binds to the surface. Work has been done to develop these potentials [25].…”
Section: Potential Energy Functionmentioning
confidence: 99%
“…This potential accurately describes the short-range, repulsive interactions which determine the collisional energy-transfer, but not the longrange intermolecular potential. The latter describes the attractive interaction of the peptide ion with the surface and is necessary to model soft-landing experiments [23,24] in which the ion binds to the surface. Work has been done to develop these potentials [25].…”
Section: Potential Energy Functionmentioning
confidence: 99%
“…Gas phase separation of isomeric species has also been achieved through ion mobility techniques (19), which could be used as a further purification method. Furthermore, methods for collecting peptides and proteins in the gas phase have been developed based on softlanding techniques (20)(21)(22), which have even been extended to create microarrays of protein ions (23) from a mass spectrometer. By activating the carboxyl group of amino acids or peptides with NHS or sulfoNHS esters and protecting reactive functionalities, such as the amines, with gas phase-labile protecting groups, we generate a reagent that can be covalently attached to the N terminus of an existing unprotected peptide, which we call the "anchor" peptide.…”
mentioning
confidence: 99%
“…For example, protein adsorption on substrates is a highly dynamic process that is strongly influenced by Coulomb interactions, hydrogen bonding, and relatively weak noncovalent interactions. These processes are highly dependant on the primary and the highorder structure of the protein and on the properties of the surface and the solvent.It has recently been demonstrated that soft-landing (SL) of mass-selected ions on surfaces is a useful mass spectrometric approach for probing details of this intrinsic behavior of immobilized biological molecules that removes the strong effects of solvents [3][4][5]. SL is defined as intact capture of mass-selected polyatomic ions on substrates [6,7] and has already been successfully used to study charge retention by small closedshell ions [6 -9] and peptide and protein ions deposited onto self-assembled monolayer surfaces (SAMs) [10 -13].…”
mentioning
confidence: 99%